Methylene blue sensitized photo Fenton-like reaction for rapid RAFT polymerization in aqueous solution. Issue 6 (24th January 2023) - Fan, Jiangtao; Li, Cuiting; Guo, Xie; Deng, Yuanming
Abstract : Rapid aqueous RAFT polymerization of acrylamides (DMA, NAM) with good oxygen tolerance initiated by ˙OH generated from methylene blue (MB) activated decomposition of H2 O2 under red light irradiation is presented. Abstract : In this work, reversible addition–fragmentation polymerization of acrylamides initiated by a photo-Fenton-like reaction is reported. Methylene blue was used as a photo sensitizer for H2 O2 activation under red light irradiation to generate hydroxyl free radicals for polymerization initiation, which brought temporal controllability to normal Fenton initiation. Successful aqueous RAFT polymerization of DMA and NAM was achieved within 20 min in an open-to-air system, giving high monomer conversion of up to 97% and a polymer with a narrow molecular weight distribution and high fidelity. A multi-block copolymer was obtained through the consecutive addition of monomers. The effect of the initiation component on the polymerization was investigated, and it was concluded that there is a complex effect of MB on the polymerization including H2 O2 activation, oxygen elimination, free radical capture, etc. The results of Electron spin resonance applied for free radical monitoring revealed that the production of the hydroxyl free radical was a response to the initiation. Despite the relatively short storage life of the current combination, we believe that this photo-Fenton-like initiated RAFT polymerization will have some applications, such as in 3D printing, the biomedical field, continuous polymerization, etc.